Transsexuality and the criminal law - Mohamad Yunus, Mohamad Ismail (Royal Malaysia Police, 2012)
By virtue of section 375 of the Malaysian Penal Code (MPC), it is clearly stated that the offence of rape could only be committed by a man (as defined in section 10 MPC) as principal upon a woman (as defined in section 10 MPC) as victim. This provision highlights that in Malaysia, the law of rape is entirely gender delineated. A question might arise, how about if a biological male who underwent the gender reassignment surgery or transsexual operation and consequently become a person with an artificial female genitalia and the issue is whether that person would remain as a male for the purposes of criminal law, and thus could not be the victim of the offence of rape?